A bibliometric analysis of the triads between intellectual property rights, foreign direct investments, and entrepreneurship - Melba Judieth Fernandes; Sunil Kumar Ambrammal (Journal of Innovation and Entrepreneurship)
Abstract Intellectual Property Rights (IPRs), Foreign Direct Investments (FDI), and Entrepreneurship (ENT) have been a researcher’s paradise and have led to a plethora of research in each of these individual domains. The intertwining of these three areas over the last few decades has been emerging and is evidencing significant factors that can drive the world's economies to prosperity. As the world staggers to regain its feet from the raging pandemic that humbled significant world economies, the need for this triad has grabbed the limelight for world economies to survive and sustain. A vivacious link exists between them, as they are the inherent contributors to Economic Growth and Development. This paper is a humble add-on to the research of the triads between IPR, FDI, and ENT and tries to unravel the scientific contribution (Academic work) through a bibliometric analysis of the nexus between IPR, FDI, and ENT. It aims to analyze the distribution of articles over the years, across different countries providing insights into the trends and patterns observed in the publication landscape. The article looks to deliver insights through diagrammatic inferences using VOSViewer into how the nexus has fashioned research in this domain. It would reference young researchers concerning publications supplemented with meaningful metrics and statistics.